Carbon‐Supported Single Atom Catalysts for Electrochemical Energy Conversion and Storage. Issue 48 (21st August 2018) - Peng, Yi; Lu, Bingzhang; Chen, Shaowei
Abstract: Single atoms of select transition metals supported on carbon substrates have emerged as a unique system for electrocatalysis because of maximal atom utilization (≈100%) and high efficiency for a range of reactions involved in electrochemical energy conversion and storage, such as the oxygen reduction, oxygen evolution, hydrogen evolution, and CO2 reduction reactions. Herein, the leading strategies for the preparation of single atom catalysts are summarized, and the electrocatalytic performance of the resulting samples for the various reactions is discussed. In general, the carbon substrate not only provides a stabilizing matrix for the metal atoms, but also impacts the electronic density of the metal atoms due to strong interfacial interactions, which may lead to the formation of additional active sites by the adjacent carbon atoms and hence enhanced electrocatalytic activity. This necessitates a detailed understanding of the material structures at the atomic level, a critical step in the construction of a relevant structural model for theoretical simulations and calculations. Finally, a perspective is included highlighting the promises and challenges for the future development of carbon‐supported single atom catalysts in electrocatalysis. Abstract : Single atom catalysts (SACs) have emerged as effective catalysts for various reactions in electrochemical energy conversion and storage. The catalytic activity is primarily ascribed to the unique electronic properties of the metal atoms and strong interfacial interactions with the supporting substrates. Recent progress of carbon‐supported SACs toward the oxygen reduction, hydrogen evolution, oxygen evolution, and CO2 reduction reactions is summarized.